2013
DOI: 10.1603/en13062
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Vector Preference Aids the Spread of Plant Pathogens: Results From a Model

Abstract: Vectors of several economically important plant viruses have been shown to feed or settle preferentially on either infected or noninfected host plants. Recent research has revealed that the feeding or settling preferences of insect vectors can depend on whether a vector is inoculative (carries the virus). To explore the implications of such changes in vector preference for the spread of the pathogen, we create a basic model of disease spread, incorporating vector preferences for infected and noninfected plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 63 publications
(80 reference statements)
8
65
0
Order By: Relevance
“…These results are consistent with those from the model by Roosien et al. (), that indicated that pathogen spread throughout an epidemic was enhanced when viruliferous vectors preferred healthy plants and nonviruliferous vectors preferred infected plants.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results are consistent with those from the model by Roosien et al. (), that indicated that pathogen spread throughout an epidemic was enhanced when viruliferous vectors preferred healthy plants and nonviruliferous vectors preferred infected plants.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that pathogen spread is slow when vectors prefer hosts that match their infection status (viruliferous vectors prefer infected hosts and nonviruliferous vectors prefer healthy hosts), and fastest when vectors prefer hosts with different infection status (viruliferous vectors prefer healthy hosts and nonviruliferous vectors prefer infected hosts). These results are consistent with those from the model by Roosien et al (2013), that indicated that pathogen spread throughout an epidemic was enhanced when viruliferous vectors preferred healthy plants and nonviruliferous vectors preferred infected plants.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations